Effect of the existence of under drain on Uplift pressure and Exit Gradient. - Al-Suhili, Rafa Hashim; Hussien, Goran O. (Sulaimani Journal for Engineering Sciences, 2017)
The effects of the existence of an under drain pipe beneath the foundation of a hydraulic structure, on both the uplift pressure under the structure and the exit gradient on its downstream side are investigated. More specifically the effect of the horizontal and vertical locations and the diameter of this under drain pipe were investigated. The Geo-Studio Seep/w software is used for simulating different geometrical configurations of a typical hydraulic structure model. Results indicate that the existence of this drain will reduce the pressure head beneath the foundation of the structure. The observed reduction in uplift pressure is found huge. As the drain diameter increases the pressure head decrease more and more. This results in a required volume against overturning to decrease with using greater diameter which is tend to 100% decrease in (V) especially where the under drain location near u/s sheet pile (location –D-). The exit gradient decrease with using drain pipe near upstream sheet pile but it increase where the drain pipe below downstream sheet pile especially (location-G-) which is downstream length of protection (L) increase from (2.837m for without drain) to (4.70 m with location G) that means about 65.67% increase.
Keywords: under drain; Hydraulic Structures; foundation